MYBIOTA: A birth cohort on maternal and infant microbiota and its impact on infant health in Malaysia - Eow, Shiang Yen; Gan, Wan Ying; Jiang, Tiemin; Loh, Su Peng; Lee, Ling Jun; Chin, Yit Siew; Than, Leslie Thian Lung; How, Kang Nien; Thong, Pui Ling; Liu, Yanpin; Zhao, Junying; Chen, Lijun (Frontiers in Nutrition, 2022)
Background: The microbiota plays a key role in early immunity maturation that affects infant health and is associated with the development of non-communicable diseases and allergies in later life. Objective: The MYBIOTA is a prospective mother-infant cohort study in Malaysia aiming to determine the association between gut microbiota with infant health (temperament, gastrointestinal symptoms, eczema, asthma and developmental delays) in Selangor, Malaysia. Methods: Pregnant mothers will be enrolled in their first trimester of pregnancy, and a follow-up will be done for infants during their first year of life. Maternal-infant biological samples (blood, feces, saliva, urine, and breast milk), anthropometric, dietary, and clinical information will be collected at different time points from early pregnancy to 12 months postpartum. Discussion: This study could provide a better understanding of the colonization and development of the gut microbiome during early life and its impact on infant health. Trial registration: Clinical Trials ID: NCT04919265. First Submitted: June 9, 2021 (https://clinicaltrials.gov/).